2004
DOI: 10.1083/jcb.200310061
|View full text |Cite
|
Sign up to set email alerts
|

YSK1 is activated by the Golgi matrix protein GM130 and plays a role in cell migration through its substrate 14-3-3ζ

Abstract: The Golgi apparatus has long been suggested to be important for directing secretion to specific sites on the plasma membrane in response to extracellular signaling events. However, the mechanisms by which signaling events are coordinated with Golgi apparatus function remain poorly understood. Here, we identify a scaffolding function for the Golgi matrix protein GM130 that sheds light on how such signaling events may be regulated. We show that the mammalian Ste20 kinases YSK1 and MST4 target to the Golgi appara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
276
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(288 citation statements)
references
References 53 publications
11
276
0
1
Order By: Relevance
“…Although Mst2 is most closely related to Drosophila Hpo and capable of functional complementation (Wu et al, 2003), it seemed possible that other Mst family members could carry out similar functions. We therefore tested two additional Mst kinases for their ability to activate Lats kinases in vitro, notably Mst1, a close homolog of Mst2, and Mst4, a more distant family member implicated in cell migration and polarization (Preisinger et al, 2004). Using the IVT assay described above, we found that both FLAG-Mst2 and Mst1 were able to activate myc-Lats1, whereas Mst4 produced little, if any, activation ( Figure 4b, top row).…”
Section: Specific Activation Of Lats1 and Lats2 By Mst2/1 Kinasesmentioning
confidence: 99%
“…Although Mst2 is most closely related to Drosophila Hpo and capable of functional complementation (Wu et al, 2003), it seemed possible that other Mst family members could carry out similar functions. We therefore tested two additional Mst kinases for their ability to activate Lats kinases in vitro, notably Mst1, a close homolog of Mst2, and Mst4, a more distant family member implicated in cell migration and polarization (Preisinger et al, 2004). Using the IVT assay described above, we found that both FLAG-Mst2 and Mst1 were able to activate myc-Lats1, whereas Mst4 produced little, if any, activation ( Figure 4b, top row).…”
Section: Specific Activation Of Lats1 and Lats2 By Mst2/1 Kinasesmentioning
confidence: 99%
“…While MST3 is involved in apoptosis, 52 STK25 is involved in cell migration and adhesion. [53][54][55] MST4 was identified as a novel member of the GCK family of STE20 kinases in 2001 and was found to be highly expressed in placenta, thymus and peripheral blood leukocytes. 56,57 The structures of the kinase domains have been determined yet the biological functions of GCK-III in particular remain elusive.…”
Section: Gck-iii Kinases As Immerging Novel Immune Regulatorsmentioning
confidence: 99%
“…95 GCK-III kinases may target the Golgi apparatus through binding with GM130 ( Figure 3). 53,96 Despite forming a stable complex, PDCD10 and Striatin may differentially regulate GCK-III. For example, PDCD10 knockdown promotes Golgi localization of MST4 in HeLa cells.…”
Section: Gcks In Immune Regulationmentioning
confidence: 99%
“…In addition to lateral cross-bridging of Golgi ministacks, GM130/GRASP65 complexes, and possibly golgin45/GRASP55 complexes, also associate with numerous factors on the cytoplasmic face of the Golgi apparatus, including the protein kinases Ysk1, Mst4, and PLK1 (Preisinger et al, 2004;Preisinger et al, 2005). Regulation of these associated factors, rather than Golgi unlinking per se, may be the mechanism facilitating G 2 /M.…”
Section: Mek1-mediated Golgi Unlinkingmentioning
confidence: 99%